Peronism Without Peron: Unions, Parties, and Democracy in Argentina - Newton, Ron (Labour / Le Travail, 1999)
The article reviews the book, "Peronism Without Peron: Unions, Parties, and Democracy in Argentina," by James W. McGuire.